Anxiety and use of cognitive emotion regulation strategies within the foreign language classroom - Ayllón Salas, Patricia; Olmo Espinosa, Alicia; Fernández Martín, Francisco D. (Porta Linguarum An International Journal of Foreign Language Teaching and Learning, 2024)
The aims of this study were to identify the existent levels of foreign language learning anxiety in students of the sixth grade of Primary Education of different bilingual and non-bilingual schools, and to determine which cognitive emotion regulation strategies these students would use in a hypothetical stressful situation. For this purpose, anxiety in Foreign Language Class and cognitive emotion regulation strategies were measured to the students (n = 262). The descriptive analysis of the obtained results led to the following conclusions: the levels of anxiety were higher in the non-bilingual sample; however, these students made more use of cognitive emotion regulation strategies.